2021
DOI: 10.1111/1753-0407.13239
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor methylation attenuates the association between physical activity and type 2 diabetes mellitus: A case‐control study

Abstract: Background Physical activity and vitamin D receptor (VDR) have been associated with type 2 diabetes mellitus (T2DM). However, the associations of VDR methylation with T2DM and physical activity remained unknown. We aimed to investigate whether VDR methylation was a link between physical activity and T2DM. Methods A 1:1 matching case‐control study was designed based on the Henan Rural Cohort Study, including 272 pairs of T2DM patients and nonpatients. Physical activity level was assessed using the International… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These results suggest that VDR methylation could attenuate the association between physical activity and T2DM. Moreover, the increased methylation levels of the VDR were also associated with decreased levels of serum insulin, confirming its pivotal role in modulating T2DM phenotype [ 44 ] ( Figure 2 ). All these preliminary data encourage additional research on the role of VDR methylation in the above-mentioned diseases, which is still poorly explored.…”
Section: Other Diseasesmentioning
confidence: 87%
See 1 more Smart Citation
“…These results suggest that VDR methylation could attenuate the association between physical activity and T2DM. Moreover, the increased methylation levels of the VDR were also associated with decreased levels of serum insulin, confirming its pivotal role in modulating T2DM phenotype [ 44 ] ( Figure 2 ). All these preliminary data encourage additional research on the role of VDR methylation in the above-mentioned diseases, which is still poorly explored.…”
Section: Other Diseasesmentioning
confidence: 87%
“…However, these preliminary analyses need to be further explored as they represent the only bibliographic data available to date on the role of VDR methylation in recurrent stone formation. In the context of T2DM, VDR methylation has also been analyzed in association with physical activity in a 1:1 matching case–control study [ 44 ]. The HRM approach was performed to determine the methylation levels of the VDR promoter in a 300 bp region comprissing 27 CpGs, both in 272 T2DM patients and healthy CTRs.…”
Section: Other Diseasesmentioning
confidence: 99%
“…Previous studies also reported that the DNA methylation of CYP24A1, CYP27B1, and VDR showed no significant differences in diabetic patients compared with the health control subjects. 18 , 24 , 25 Cavitation is a severity result of pulmonary tuberculosis, which is related to poor prognosis, treatment relapse, higher infectious rates, and development of drug resistance. 26 Our results demonstrated that the DNA methylation profile of all genes selected in patients with TB-DM was not related to three common abnormal CT features, single cavity, multiple cavities, and air bronchogram sign, referring to the methylation status of the candidate genes in the vitamin D metabolic pathway might not affect the prognosis and relapse of TB-DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study in China has proved that DNA methylation of vitamin D might not be involved in the pathogenesis of DM. 24 , 25 Wang et al in their study demonstrated that methylation levels of key genes in the vitamin D metabolic pathway are related to the risk and prognosis of tuberculosis. 14 Additionally, in the meantime, we are conducting this study, there is a rigorous anti-covid-19 battle going on in China, which disturbs our experimental program.…”
Section: Discussionmentioning
confidence: 99%
“…However, these preliminary analyses need to be further explored as they represent the only bibliographic data available to date on the role of VDR methylation in recurrent stone formation. In the contest of T2DM, VDR methylation has also been analysed in association with physical activity in a 1:1 matching case-control study [41]. HRM approach was performed to determine the methylation levels of VDR promoter in a 300 bp region comprising 27 CpGs, both in 272 T2DM patients and healthy CTRs.…”
Section: Other Diseasesmentioning
confidence: 99%